Regioselective N‐Functionalization of Tautomerizable Heterocycles through Methyl Trifluoromethanesulfonate‐Catalyzed Substitution of Alcohols and Alkyl Group Migrations. Issue 4 (18th January 2022) - Duari, Surajit; Biswas, Subrata; Roy, Arnab; Maity, Srabani; Mishra, Abhishek Kumar; de Souza, Aguinaldo R.; Elsharif, Asma M.; Morgon, Nelson H.; Biswas, Srijit
Abstract: A catalytic synthetic strategy has been developed combining two protocols, such as, direct nucleophilic substitution of alcohols followed by X ‐ to N ‐ alkyl group migration ( X = O, S ) to access N ‐functionalized benzoxazolones, benzothiazolethiones, indolinone, benzoimidazolethiones, and pyridinones derivatives. Methyl trifluoromethanesulfonate (MeOTf) was found to catalyze the reaction, which revealed the catalytic property of MeOTf. A mechanism was established through experiments as well as DFT calculations wherein the −OH group of alcohols were converted to the corresponding −OMe groups and in situ generated TfOH. The −OMe groups produced underwent TfOH catalyzed − X alkylation ( X = O, S ) of the heterocycles followed by − X‐ to − N‐ alkyl group migrations in a single step. Abstract :